SEJARAH PERKEMBANGAN MAZHAB NAHWU ARAB (SEBUAH TINJAUAN HISTORIS) (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2017)
This paper describes the history of development of Arab syntax. In the classical Islamic vocabulary of Arabic syntax (famous among academic and non-academic) "Nahwu". History of early the development of nahwu can not be separated from school of thought (mazhab) of Basra and Kufa. Furthermore, that expand to Bagdad, Andalusia and Egypt. The polemic of nahwu thought is seen in schools respectively. Some of thoughts the above five schools are based on reasonable arguments and propositions. Result for this study, the school of thought "Nahwu" of Basra and Kufa are the founders of Arabic syntax.